2019
DOI: 10.7759/cureus.5571
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Tumor: A Rare, Aggressive Tumor of the Gallbladder

Abstract: We report a case of rare and aggressive gallbladder neuroendocrine carcinoma (GB-NEC), diagnosed with the help of endoscopic ultrasound (EUS). A 65-year-old asymptomatic male, with a past medical history of hypertension, underwent abdominal ultrasound for the screening of an abdominal aortic aneurysm. He was found to have a mixed echogenicity area near the stomach, an incidental finding on abdominal ultrasound. The patient had an upper gastrointestinal (GI) endoscopy exam, which revealed an antral mass that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…Diagnostic comparisons indicate that immunohistochemical staining is the most effective tool for the diagnosis of GB-NENs. Immunohistochemistry is divided into two parts (32). First, neuroendocrine cell markers such as neuron-specific enolase (NSE), synaptophysin (Syn), pheochromin-A (CHG-A), protein gene product and Rankine are positively detected (Fig.…”
Section: Diagnosismentioning
confidence: 99%
“…Diagnostic comparisons indicate that immunohistochemical staining is the most effective tool for the diagnosis of GB-NENs. Immunohistochemistry is divided into two parts (32). First, neuroendocrine cell markers such as neuron-specific enolase (NSE), synaptophysin (Syn), pheochromin-A (CHG-A), protein gene product and Rankine are positively detected (Fig.…”
Section: Diagnosismentioning
confidence: 99%
“…Considering the subtypes, it is conventionally thought that most neuroendocrine neoplasms (NENs) of the gallbladder are NECs, and that NECs are predominantly small cell neuroendocrine carcinomas (SCNECs). [8][9][10][11] Some case reports and case series published recently reported that the proportions of SCNEC and large cell neuroendocrine carcinoma (LCNEC) of gallbladder are similar. 7,12 Compared with gallbladder ADCs, the general demographic features of gallbladder NECs such as age, sex, and BMI are similar.…”
Section: Introductionmentioning
confidence: 99%
“…At the time of diagnosis, most of them were at advanced stages. Considering the subtypes, it is conventionally thought that most neuroendocrine neoplasms (NENs) of the gallbladder are NECs, and that NECs are predominantly small cell neuroendocrine carcinomas (SCNECs) 8–11 . Some case reports and case series published recently reported that the proportions of SCNEC and large cell neuroendocrine carcinoma (LCNEC) of gallbladder are similar 7,12 …”
Section: Introductionmentioning
confidence: 99%
“…The exclusion criteria of the studies for literature review were as follows: (a) primary lesion arising from organs other than the gallbladder; (b) histological subtype of GB‐NET was not pathologically confirmed; (c) studies on GB‐NET or well‐differentiated MiNEN; (d) review articles, meta‐analyses, editorials, commentaries, or animal studies, etc; (e) the required clinicopathological data could not be extracted; and (f) insufficient data on the follow‐up or patient outcomes. After literature search data of additional 47 patients from 38 studies were obtained 5,7,9–44 . Finally, a total of 62 patients with GB‐NEC including poorly differentiated MiNEN were finally enrolled.…”
Section: Methodsmentioning
confidence: 99%